EFEKTIFITAS PENGELOLAAN KAS DAERAH DALAM PENINGKATAN PENDAPATAN ASLI DAERAH - Sinaga, Hasan Bakri; Heriyanto, Meyzi; Safri, Indra (Jurnal Ilmu Administrasi Negara, 2018)
Effectiveness of Regional Cash Management in Increasing Original Regional Income. This study aims to determine the effectiveness of local cash management in an effort to increase the original revenue. This type of research is evaluative research. The research informants are PPKD, BUD authority and treasurer of PPKD acceptance. Data collection is used in the form of documentation, interview and observation. Data analysis using Ishikawa diagram (fishbone analysis model) draws conclusions on the weaknesses of conditions found during the study, analyzes the causes of the problems, assesses their impact, and sees whether or not improvements are made. The results show that the Cash Management of Riau Province Government Year 2014 and 2015 has been effective in increasing PAD.